Abusive Administration: A Case Study - Anne L. Jefferson (Educational Considerations, 2006)
In the academic world, there is an assumption of reasonable administrative conduct. In fact, to ensure such conduct, universities, like other public institutions, may have collective agreements to reinforce this assumption.
Keywords: administration; abusive; Case Study; faculty